2019
DOI: 10.3390/nu11030569
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension Associated with Fructose and High Salt: Renal and Sympathetic Mechanisms

Abstract: Hypertension is a leading cause of cardiovascular and chronic renal disease. Despite multiple important strides that have been made in our understanding of the etiology of hypertension, the mechanisms remain complex due to multiple factors, including the environment, heredity and diet. This review focuses on dietary contributions, providing evidence for the involvement of elevated fructose and salt consumption that parallels the increased incidence of hypertension worldwide. High fructose loads potentiate salt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
39
1
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 78 publications
(110 reference statements)
0
39
1
1
Order By: Relevance
“…Soncrant et al reported that elevated BP was increased by sympathoexcitation in 20% fructose-induced, salt-sensitive, hypertensive rats [33]. It has been shown that the ingestion of fructose altered the secretion of hormones that regulate energy balance associated with increased SNA [34]. However, in the current study, although a DGAT1 inhibitor was administered orally to block triglycerides production, sympathoexcitation was not inhibited in fructose-fed rats.…”
Section: Discussioncontrasting
confidence: 55%
“…Soncrant et al reported that elevated BP was increased by sympathoexcitation in 20% fructose-induced, salt-sensitive, hypertensive rats [33]. It has been shown that the ingestion of fructose altered the secretion of hormones that regulate energy balance associated with increased SNA [34]. However, in the current study, although a DGAT1 inhibitor was administered orally to block triglycerides production, sympathoexcitation was not inhibited in fructose-fed rats.…”
Section: Discussioncontrasting
confidence: 55%
“…Excess salt intake has been linked to many chronic diseases, including hypertension, cardiovascular disease, kidney dysfunction, and osteoporosis [2][3][4][5]. While an increase in salt-enriched "fast food" consumption has been considered a putative factor for many pathological conditions, there is no (animal or human) data available to delineate whether a long-term high-salt diet (HSD) may disturb pain sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…High-fructose corn syrup (HFCS) is the main source of added sweeteners in sweetened beverages. A high intake of HFCS causes an increase in BP and thus involves an increase in uric acid production which, in turn, results in a lowering of nitric oxide in the body [43,44]. Other hypotheses behind high SSB intake being implicated in hypertension involve decreased sodium excretion, activation of the sympathetic nervous system [45,46], or an increased sodium concentration in the body through increased gut absorption [47].…”
Section: Discussionmentioning
confidence: 99%